Assessing the jobs-environment relationship with matched data from US EEOC and US EPA - Michael Ash; James K. Boyce (University of Massachusetts, Department of Economics, 2016)
Using matched facility-level data from the US EPA Toxics Release Inventory (TRI) and the US Equal Employment Opportunity Commission EEO-1 database, we assess (1) the trade-off between jobs and environmental quality and (2) the extent to which the distribution of the benefits of employment in industrial production mirrors the distribution of the costs of exposure to hazardous byproducts of industrial activity in the dimension of race and ethnicity. We find no evidence that facilities that create higher pollution risk for surrounding communities provide more jobs in aggregate. The share of pollution risk accruing to ethnic or racial minority groups typically exceeds the share of employment and substantially exceeds the share of good jobs held by members of those groups.
Keywords: 330